2008
DOI: 10.1016/j.pathophys.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and vascular dysfunction

Abstract: One of the most profound challenges facing public health and public health policy in Western society is the increased incidence and prevalence of both overweight and obesity. While this condition can have significant consequences for patient mortality and quality of life, it can be further exacerbated as overweight/obesity can be a powerful stimulus for the development of additional risk factors for a negative cardiovascular outcome, including increased insulin resistance, dyslipidemia and hypertension. This m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(137 citation statements)
references
References 148 publications
(211 reference statements)
1
129
2
5
Order By: Relevance
“…[15][16][17]61,62 Among the adipose tissue-derived substances, pL has multiple actions that are potentially relevant not only for the control of body fat but also for physiological and pathophysiological cardio-renal regulation. 35,63 Elevated plasma pL level has been associated with hypertension in both lean and overweight/obese hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17]61,62 Among the adipose tissue-derived substances, pL has multiple actions that are potentially relevant not only for the control of body fat but also for physiological and pathophysiological cardio-renal regulation. 35,63 Elevated plasma pL level has been associated with hypertension in both lean and overweight/obese hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] The progression and persistence of obesity have been associated with a progressive alteration of the function and the structure of the vascular wall, including chronic inflammation, endothelial dysfunction, alteration of vascular tone and reactivity, proliferation of smooth muscle cells, neo-angiogenesis and altered patterns of blood flow regulation with both hypertensive and arteriosclerotic consequences. [15][16][17] Some of the metabolic, endocrinologic and hemodynamic changes associated with obesity and hypertension are partially reversed by BW reduction, which decreases BP in overweight non-obese hypertensive patients. Numerous trials of hypertension treatment have shown that weight loss, whether alone or in combination with antihypertensive drugs, has a beneficial effect on BP control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ET axis has been shown to have a role in the growth and progression of several tumor types, including lung cancer (Bhalla et al, 2009) ET-B receptors, such as lung tumors (Ahme et al, 2000). The rat model used in this study is a valuable model for the study of obesity in humans since it offers many features similar to those of human obesity, such as moderate hypertension, hypertriglyceridemia, and insulin resistance, all features of metabolic syndrome (Stapleton et al, 2008). In this study, the overexpression of ET-1, together with the ET-A and ET-B upregulation, was observed in O AH , in line with previous studies on solid tumors (Nakamuta et al, 1993;Kajima and Nihei, 1995;Nelson et al, 1996;Shankar et al, 1998;Bagnato et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…While the above findings clearly suggest some evidence for the "paracrine" role of PVAT [12] , a more vigor experimental approach is still necessary to unequivocally define the role of adipocyte-derived factors. The predominant finding of the inhibitory effect of ADRF on the vascular reactivity appears to argue against the exaggerated vascular reactivity or reduced endothelium-dependent relaxation commonly found to be linked with obesity-associated hypertension or metabolic syndrome [13] . It is worthwhile to mention that periaortic fat tissue has been found to stimulate vascular smooth muscle cells proliferation, a structural characteristics consistent with vascular changes associated with aging and obesity [14] .…”
Section: Perivascular Adipocytes: Diffusible Factors and Control Of Vmentioning
confidence: 98%